Impact of Antipsychotic Medications on Weight Gain and Eating Disorder-Related Psychopathology in Adult Inpatients with Anorexia Nervosa - Bauman, Tabea; Kolar, David R.; Correll, Christoph U.; Haas, Verena; Voderholzer, Ulrich (Pharmacopsychiatry, 2024)
Introduction The impact of antipsychotic use on weight gain and eating disorder-related psychopathology in adult inpatients with anorexia nervosa (AN) is unclear.Methods Consecutively hospitalized adults with AN were retrospectively analyzed. Co-primary outcomes were body mass index (BMI) and weekly weight change. Secondary outcomes were Eating Disorder Inventory-2 (EDI-2) subscale scores ‘drive for thinness’ and ‘body dissatisfaction’. Admission-to-discharge changes were compared in patients continuing pre-admission antipsychotics (APcont), starting antipsychotics (APnew) and patients without psychopharmacotherapy (noMed) using linear mixed models. Sensitivity analyses were conducted in subgroups matched for age, length of stay, baseline BMI and baseline EDI-2 scores. Subgroups were also compared regarding BMI trajectories, using non-linear growth curve models. Within-group analyses compared weight gain before vs. after the median antipsychotic onset week.Results Of 775 adult inpatients (mean length of stay =103.5±48.0 days), 21.7% received antipsychotics (APcont =7.7%; APnew=13.9%), i. e., olanzapine (n=127, dose =5.5±3.1 mg/day) or quetiapine (n=41, dose=100.0±97.7 mg/day), while 78.3% did not receive any medication. Comparing all three groups, a significant time×group interaction was found for noMed and APnew vs. APcont (p=0.011), but this effect disappeared when comparing matched subgroups. However, in matched subgroups (n=54 each) APnew showed steeper weight gain vs. APcont both overall (p=0.011) and after median antipsychotic initiation (5.8±5.0 weeks) (p≤0.001). No significant group differences emerged in EDI-2 subscale scores.Discussion In this naturalistic study, 22% of adult inpatients received antipsychotics. However, neither weight gain nor AN-related psychopathology changed differently in patients treated with vs. without antipsychotics. Newly initiated antipsychotic treatment vs. continuation from pre-admission had better weight gain outcomes.
Keywords: anorexia nervosa; adults; inpatients; weight gain; antipsychotics